2023
DOI: 10.1109/tasc.2023.3246430
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward Superconductor Electronics Fabrication Process With Planarized NbN and NbN/Nb Layers

Abstract: In order to increase circuit density of superconductor digital and neuromorphic circuits by 10× and reach integration scale of 10 8 Josephson junctions (JJs) per chip, we developed a new fabrication process on 200-mm wafers, using self-shunted Nb/Al-AlOx/Nb JJs and kinetic inductors for cell miniaturization. The process has one layer of JJs, one layer of resistors, and ten fully planarized superconducting layers: 8 niobium layers and two layers of high kinetic inductance materials, Mo2N and NbN, with sheet ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…To alleviate resolution limitations, the SC1 process has been recently modified to include a 193 nm photolithography using an ASML PAS5500-1100 scanner [32] to pattern a layer of JJs, J5, and critical layers of inductors, whereas keeping the rest of the fabrication process identical to the SC1. This resulted in a new node, titled SC2, with 150 nm minimum linewidth for critical inductors and 500 nm minimum diameter of JJs in circuits.…”
Section: Description Of Fabrication Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…To alleviate resolution limitations, the SC1 process has been recently modified to include a 193 nm photolithography using an ASML PAS5500-1100 scanner [32] to pattern a layer of JJs, J5, and critical layers of inductors, whereas keeping the rest of the fabrication process identical to the SC1. This resulted in a new node, titled SC2, with 150 nm minimum linewidth for critical inductors and 500 nm minimum diameter of JJs in circuits.…”
Section: Description Of Fabrication Processesmentioning
confidence: 99%
“…The etch rate of photoresists used for 193 nm photolithography is higher, and selectivity to Nb is lower, than that of 248 nm photoresists. This necessitates the use of a hard mask process [32], shown schematically in figure 1. Changing multiple critical fabrication processes required reevaluation and calibration of circuit structures, including inductors.…”
Section: Description Of Fabrication Processesmentioning
confidence: 99%
“…Dependences of the resistivity, 𝜌𝜌, and superconducting critical temperature, 𝑇𝑇 𝑐𝑐 of the reactively sputtered NbN x films on the deposition parameters in the Endura PVD system were studied in [22]. It was observed that the resistivity of NbN x films monotonically increases with increasing N 2 partial pressure, whereas superconducting films, with the highest 𝑇𝑇 𝑐𝑐 of 16 K, are only produced in a relatively narrow range of N 2 partial pressures; see [22,Fig. 5].…”
Section: Fabrication Of Nb/nbn X /Nb Trilayer Junctionsmentioning
confidence: 99%
“…Its width may coincide with the width of the composite electrode, and may be determined by the requirements for the line width of a technological process. In MIT Lincoln Laboratory technology, the lower and upper limits on W (150 nm W 250 nm) are determined by the requirement of current carrying capacity and uniformity of the bias current distribution across the width of the electrodes, respectively [79]. There are no strict requirements for the reproducibility of the gap between the electrodes formulated in [67].…”
Section: Correct Determination Of ϕ As Measured By Experimentsmentioning
confidence: 99%